(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The study aimed to identify the level of met memory and its relationship to psychological stress among Al-Quds University students. To achieve this objective, the study used the correlative descriptive approach. A stratified sample of (382) students was randomly selected. There were statistically significant differences in the level of psychological stress among the students due to gender in favor of males. There were also statistically significant differences in the level of psychological stress due to college in favor of colleges of humanities; however, no statistically significant differences in the level of psychological stress were found due to the academic level. Statistically significant differences in the met memory level were also found due to gender in favor of females. However, no statistically significant differences in the met memory level were found due to the academic level, including all domains, and due to college, including all domains, too. The results of the study showed an inverse relationship between met memory and psychological stress among Al-Quds University students.